EOQ Application Reduces PAC Inventory Cost in Water Treatment: Penerapan EOQ Mengurangi Biaya Persediaan PAC dalam Pengolahan Air - Vanisa Reyhan Faradiba; Tedjo Sukmono (Indonesian Journal of Innovation Studies, 2025)
General Background Inventory control plays a critical role in ensuring operational efficiency in water treatment systems. Specific Background Poly Aluminium Chloride (PAC) is a key chemical used in PDAM operations, requiring proper inventory management to avoid shortages and excessive costs. Knowledge Gap However, existing ordering policies often rely on frequent purchases without optimal cost considerations. Aims This study aims to analyze PAC inventory control using the Economic Order Quantity (EOQ) method to determine optimal ordering quantity and minimize total costs. Results The findings show that the optimal order quantity is 151,669.56 kg with an ordering frequency of 4 times per year, compared to 48 times under the company policy. Total inventory cost decreases from Rp54,287,987.83 to Rp7,886,816.84, resulting in significant cost savings. Safety stock is calculated at 10,199 kg and reorder point at 20,398 kg. Novelty This study applies EOQ analysis to PAC inventory in a water treatment context using real operational data. Implications The results provide a practical approach for improving inventory efficiency and reducing operational costs in water treatment companies. Keywords: Economic Order Quantity, Inventory Control, PAC Chemical, Water Treatment, Cost Optimization Key Findings Highlights Optimal order size significantly larger than current practice Ordering frequency reduced from monthly to quarterly pattern Inventory cost shows substantial reduction after method application